STUDI EKSPERIMENTAL PENINGKATAN PERPINDAHAN PANAS ALIRAN TURBULEN PADA PENUKAR KALOR PIPA KONSENTRIK DENGAN PERFORATED TWISTED TAPE INSERT WITH PARALLEL WINGS - Yaningsih, Indri; Istanto, Tri; Juwana, Wibawa Endra (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Heat transfer, flow friction and thermal performance factor characteristics in a concentric pipe heat exchanger fitted perforated twisted tape insert with parallel wings (PTPW), using water as working fluid are investigated experimentally. The design of PTPW involves the following concepts: (1) wings induce an extra turbulence near tube wall and thus efficiently disrupt a thermal boundary layer (2) holes existing along a core tube, diminish pressure loss within the tube. The experiments are conducted using the PTPW with the three wing depth ratio (w/W = 0.16, 0.24 and 0.32) and constant the hole diameter ratio (d/W) of 0.24 over a Reynolds number range of 5800–18,500. A typical twisted tape insert (TT) was also tested for a comparison. The results show that both mean Nusselt number and mean friction factor associated by all twisted tape are consistently higher than those without twisted tape (plain tube). It is also found that Nusselt number, friction factor and thermal performance factor increase with increasing wing depth ratio. Over the range considered, Nusselt number and friction factor in a concentric pipe heat exchanger with the PTPW are, respectively, 1.14–1.42 and 1.12–1.40 times of those in the tube with typical twisted tape (TT).